Multichannel electrocardiogram diagnostics for the diagnosis of arrhythmogenic right ventricular dysplasia. Issue Volume 20:Issue FI 1(2018) (29th August 2017) - Marcinkevics, Ricards; O'Neill, James; Law, Hannah; Pervolaraki, Eleftheria; Hogarth, Andrew; Russell, Craig; Stegemann, Berthold; Holden, Arun V; Tayebjee, Muzahir H
Abstract: Aims: The identification of arrhythmogenic right ventricular dysplasia (ARVD) from 12-channel standard electrocardiogram (ECG) is challenging. High density ECG data may identify lead locations and criteria with a higher sensitivity. Methods and results: Eighty-channel ECG recording from patients diagnosed with ARVD and controls were quantified by magnitude and integral measures of QRS and T waves and by a measure (the average silhouette width) of differences in the shapes of the normalized ECG cycles. The channels with the best separability between ARVD patients and controls were near the right ventricular wall, at the third intercostal space. These channels showed pronounced differences in P waves compared to controls as well as the expected differences in QRS and T waves. Conclusion: Multichannel recordings, as in body surface mapping, add little to the reliability of diagnosing ARVD from ECGs. However, repositioning ECG electrodes to a high anterior position can improve the identification of ECG variations in ARVD. Additionally, increased P wave amplitude appears to be associated with ARVD.